Volatile evolution during thermal treatment of oily sludge from a petroleum refinery wastewater treatment Plant: TGA-MS, Py-GC(EGA)/MS and kinetics study. (15th October 2020) - Nie, Fan; Li, Yuguo; Tong, Kun; Wu, Baichun; Zhang, Mingdong; Ren, Wen; Xie, Shuixiang; Li, Xingchun
Graphical abstract: Highlights: The volatile evolution during thermal treatment of an oily sludge was discussed. Internal diffusion had a great influence on the reaction rate during 120–360 °C. The proportion of light and unsaturated hydrocarbons increased during 360–550 °C. The evolution profiles of typical compounds in volatile were characterized. Abstract: The volatile evolution during thermal treatment of an oily sludge derived from petroleum refinery wastewater treatment plant was investigated by in-situ pyrolytic and kinetic analysis. According to kinetic mechanism model, it was found that the internal diffusion had a great influence on volatile release during 120–360 °C, while the devolatilization rate during 360–550 °C would more depend on the concentration of remaining hydrocarbons. By Py-GC/MS, oils were trapped and analyzed respectively during 60–360 °C and 360–550 °C, and above 300 compounds were identified and semi-quantified of the volatiles. During 60–360 °C, the detected volatile was mainly composed of saturated aliphatics, accounting for 68.69%. More proportion of light chain aliphatic hydrocarbons and monoaromtics were observed during 360–550 °C, and the relative content of unsaturated aliphatics increased to 33.81%. From the evolution profiles of typical oil products, the volatile release during 120–360 °C would follow the order of molecular weight. But during 360–550 °C, as a result of increasing thermal-cracking degree, the release peaks of the different volatile species were corresponded to similar temperature. The gaseous and sulfur-containing compounds were also traced. Among them, CO2 was the main product above 550 °C for the decomposition of minerals, and sulfur-containing compounds were mainly generated during < 450 °C.